Unexpected Inhibitory Effect of Octenidine Dihydrochloride on Candida albicans Filamentation by Impairing Ergosterol Biosynthesis and Disrupting Cell Membrane Integrity - Ting Fang; Juan Xiong; Li Wang; Zhe Feng; Sijin Hang; Jinhua Yu; Wanqian Li; Yanru Feng; Hui Lu; Yuanying Jiang (MDPI AG, 2023)
Candida albicans filamentation plays a significant role in developing both mucosal and invasive candidiasis, making it a crucial virulence factor. Consequently, exploring and identifying inhibitors that impede fungal hyphal formation presents an intriguing approach toward antifungal strategies. In line with this anti-filamentation strategy, we conducted a comprehensive screening of a library of FDA-approved drugs to identify compounds that possess inhibitory properties against hyphal growth. The compound octenidine dihydrochloride (OCT) exhibits potent inhibition of hyphal growth in C. albicans across different hyphae-inducing media at concentrations below or equal to 3.125 μM. This remarkable inhibitory effect extends to biofilm formation and the disruption of mature biofilm. The mechanism underlying OCT's inhibition of hyphal growth is likely attributed to its capacity to impede ergosterol biosynthesis and induce the generation of reactive oxygen species (ROS), compromising the integrity of the cell membrane. Furthermore, it has been observed that OCT demonstrates protective attributes against invasive candidiasis in Galleria mellonella larvae through its proficient eradication of C. albicans colonization in infected G. mellonella larvae by impeding hyphal formation. Although additional investigation is required to mitigate the toxicity of OCT in mammals, it possesses considerable promise as a potent filamentation inhibitor against invasive candidiasis.